Pengolahan Air Limbah Industri Kelapa Sawit Dengan Proses Biologi Anaerobik - Rahyani Ermawati; Walidin Walidin; Hartoyo Hartoyo (Balai Besar Kimia dan Kemasan, 1999)
Research on wastewater treatment from coconut oil by using local anaerobic bacteria was carried out by continues methods. Local anaerobic bacteria from cattle breeding farm have been acclimated by mix with chemicals for bacteria growth, The TOC load is 1,8 g!Llday, and the removal efficiency of TOC is 75 % this condition not optimal. Mixture between bacteria and waste water and also the distribution of bacteria in the wasreactor was not good there fore condition was not optimal yet. High contain of oil in the wastewater also lower the efficiency.